FROM REBEL SONGS TO MORO SONGS: POPULAR MUSIC AND MUSLIM FILIPINO PROTEST - Talusan, Mary (Humanities Diliman: A Philippine Journal of Humanities; Vol 7 No 1 (2010), 2010)
Rank-and-file supporters of the Bangsamoro rebellion (1972-1977) articulated their personal sentiments about the war in a genre called “rebel songs.” The lyrics reveal that fighters’ personal aspirations often diverged from the official aims of separatist leaders. This article examines how rebel songs transitioned into “Moro songs” in the post-martial law era and why they came to more narrowly reflect the movement’s official goals of Moro unity and Islamic renewal. While Muslim separatists hinged their ideology on the concept of a shared religion and history distinct from the rest of the Philippines, the musical vehicle they approved to convey aspirations for political and religious autonomy was not, however, indigenous genres, such as tudtol or dindiken. Rather, Moro songs set Magindanaon lyrics to the melodies of American folk, country and rock ballads—such as Bryan Adams’s “Straight from the Heart”—to frame protests against the Philippine government’s incursion into the homeland, the fight for religion and calls for Muslim unity. By endorsing this hybrid genre to broadcast separatist goals, the movement opened up a communicative space for its message to internal and external audiences, across cultural and national boundaries.
Keywords: Moro songs, Magindanao/Maguindanao, American colonialism, transnationalism, American music